Income distribution and mortality in Sweden (Italian Journal of Public Health, 2008)
Background: The hypothesis that a high income inequality on a societal level is associated with poor healthoutcomes has been both rejected and accepted in empirical studies. Whether the influence of economiccircumstances on health operates at the individual level or societal level has important implications on policyand intervention alternatives. The objective of this study was to analyse the relationship between incomeinequality and mortality in Swedish municipalities and if the relationship varies depending on the meanincome or on the time-lag between income inequality and mortality.Methods: The study was based on register data on mean income and income inequality (Gini coefficients)from Statistics Sweden 1982 and 1998, aggregated on the municipality level. Data on age-standardised deathrates per 100,000 persons were obtained for 1983, 1988, 1993, 1998 and 2002. The analysis on 1998 was atest of the robustness of the results.Results: The relationship between high income inequality in 1982 and mortality in 1983 was negative with asimilar relationship in 1998. Using latency periods, the results show a decreasing trend of mortality in relationto higher Gini coefficients. A positive relationship between Gini and mean income implies that municipalitieswith larger income distribution also had a higher mean income and vice versa.Conclusions: High income inequality does not have a negative effect on mortality in Swedish municipalities.The municipalities with high income inequality have also high mean income as opposed to many othercountries. The income level seems to be more substantial for mortality than the income inequality.
Keywords: income inequality; income level; mortality; Sweden